Brain changes: aerobic exercise for traumatic brain injury rehabilitation - Snowden, Taylor; Morrison, Jamie; Boerstra, Meike; Eyolfson, Eric; Acosta, Crystal; Grafe, Erin; Reid, Hannah; Brand, Justin; Galati, Matthew; Gargaro, Judith; Christie, Brian R. (Frontiers in Human Neuroscience, 2023)
Introduction Traumatic Brain Injury (TBI) accounts for millions of hospitalizations and deaths worldwide. Aerobic exercise is an easily implementable, non-pharmacological intervention to treat TBI, however, there are no clear guidelines for how to best implement aerobic exercise treatment for TBI survivors across age and injury severity. Methods We conducted a PRISMA-ScR to examine research on exercise interventions following TBI in children, youth and adults, spanning mild to severe TBI. Three electronic databases (PubMed, PsycInfo, and Web of Science) were searched systematically by two authors, using keywords delineated from “Traumatic Brain Injury,” “Aerobic Exercise,” and “Intervention.” Results Of the 415 papers originally identified from the search terms, 54 papers met the inclusion criteria and were included in this review. The papers were first grouped by participants’ injury severity, and subdivided based on age at intervention, and time since injury where appropriate. Discussion Aerobic exercise is a promising intervention for adolescent and adult TBI survivors, regardless of injury severity. However, research examining the benefits of post-injury aerobic exercise for children and older adults is lacking.